ANALISIS PENGELOLAAN KAWASAN PESISIR SECARA TERPADU DI KABUPATEN SERDANG BEDAGAI SUMATERA UTARA Analysis of Integrated Coastal Management in Serdang Bedagai North Sumatra - Rasyid Kurnia Nasution; Darma Bakti; Rusdi Leidonald (AQUACOASTMARINE, 2015)
Serdang Bedagai has lenght the coastline of 95km covers five districts namely, Pantai Cermin, Perbaungan, Teluk Mengkudu, Tanjung Beringin dan Bandar Khalifah. This area has great potential to be used agriculture, marine ecotourism, fisheries, and research. From every potential that exists in the Serdang Bedagai coastal, there are still some problems, especially coastal ecological damaged. This research aims to determine the strategic direction of integrated coastal management in Serdang Bedagai.The research was conducted in May-July 2014 in the coastal areas of Serdang Bedagai. This study used a purposive random sampling. There have 4 station observations, station 1 Bagan Kuala Village , station 2 Sentang Village, station 3 Sei Nagalawan Village, station 4 Pantai Cermin Kiri Village. Results of the analysis showed that the need for the arrangement of space utilization concepts in Serdang bedagai coastal in more detail, so that the land use of coastal areas can be managed with attention to the link ages between environmental aspects of coastal and local government of Serdang Bedagai need to issue policy directives based coastal management zone to create coastal management in an integrated manner.Keywords:Coastal Community, Coastal Management, Serdang Bedagai